Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1109/22.788524
|View full text |Cite
|
Sign up to set email alerts
|

Generalized analysis of coupled lines in multilayer microwave MCM-D technology-application: integrated coplanar Lange couplers

Abstract: In this paper, the design and realization of coplanar Lange couplers integrated in a multilayer thin-film multichip module deposition (MCM-D) technology is discussed. The MCM-D technology has been well established for the interconnection of high-speed digital circuits, and is now being recognized to be very useful for the integration and interconnection of microwave components. In this way, passive structures, such as spiral inductors, filters, and couplers, may be realized efficiently and more cost effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2001
2001

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…We can conclude that the prediction of the couplers performance using the quasi-TEM program and the method of Paolino is very good and better than previously published results: an amplitude balance of 0 dB was targeted in [15], while the measurements indicate an amplitude balance of 0.8 dB with a return loss of 15 dB.…”
Section: Design Methods Comparisonmentioning
confidence: 64%
See 2 more Smart Citations
“…We can conclude that the prediction of the couplers performance using the quasi-TEM program and the method of Paolino is very good and better than previously published results: an amplitude balance of 0 dB was targeted in [15], while the measurements indicate an amplitude balance of 0.8 dB with a return loss of 15 dB.…”
Section: Design Methods Comparisonmentioning
confidence: 64%
“…The multiconductor multilayered structures are analyzed using the quasi-TEM method explained in [15] and [19]. The main advantage is that the optimization of the couplers geometry can be done in a fast and efficient way.…”
Section: Quasi-tem Analysis and Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent developments have demonstrated that because of its excellent dimension control and the use of high-quality materials, this technology may be used for highfrequency analog applications. Integrated passive components [15]- [19], couplers [20], [21], baluns [21], [22], and even antennas at microwave frequencies [23]- [25] have been demonstrated in MCM-D. Furthermore, the first complete MCM-D RF subsystem demonstrator modules are also being developed [26], [27].…”
mentioning
confidence: 99%
“…The parameters of the multilayer microstrip line can be determined using an in-house developped quasi-TEM program able to calculate the transmission line parameters of a multi-conductor transmission line in a multilayer substrate. The thickness of the metal layers is also accurately taken into account 10 . The charactersitic impedances, of the intrinsic feedthrough as a function of the selected metal-layer and the stripwidth, are summarized in Table 1.…”
Section: Design Of the Intrinsic Feedthroughmentioning
confidence: 99%